2015
DOI: 10.5888/pcd12.150167
|View full text |Cite
|
Sign up to set email alerts
|

A Sex-Specific Analysis of Nutrition Label Use and Health, Douglas County, Nebraska, 2013

Abstract: IntroductionIn 2014 the US Food and Drug Administration proposed a series of changes to its 1992 guidelines on nutrition facts labeling to help consumers make informed food choices. To date, few studies have examined the association between consumers’ use of the nutrition label and health. The objective of this study was to assess the association between nutrition label use and health and to determine whether the association differs by sex.MethodsUsing data from a population-based, random sample survey of 1,50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…This may be explained by the greater interest in nutritional information and labels of these individuals compared to smokers or former smokers [ 61 ]. This finding is in line with other studies, which have noted that former or never smokers are more likely to read nutrition labels [ 61 65 ]. We also found that households with children were more likely to correctly rank the food products.…”
Section: Discussionsupporting
confidence: 93%
“…This may be explained by the greater interest in nutritional information and labels of these individuals compared to smokers or former smokers [ 61 ]. This finding is in line with other studies, which have noted that former or never smokers are more likely to read nutrition labels [ 61 65 ]. We also found that households with children were more likely to correctly rank the food products.…”
Section: Discussionsupporting
confidence: 93%
“…This is in congruence with the observation that women consume less fast food as compared with men. [30] These proportions make us understand that discretionary salt is the sole contributor to the excess salt intake in this population. Hence, any measure to reduce salt intake should focus on changing the discretionary salt use behavior in addition to avoiding food prepared outside or packed food in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Food industries opposed the implementation of TLL [ 16 ] and specialists, including nutrition and food industry experts were not sure about the impact of TLL on consumers' food choices. One of the reasons of disagreement among experts regarding the variety of label designs is due to different study results, which indicate various factors such as socio-economic status [ 20 ], gender [ 21 ], nutrition knowledge [ 22 ], dietary behavior [ 23 ], etc. to be influential.…”
Section: Introductionmentioning
confidence: 99%